2009
DOI: 10.1254/jphs.08334fp
|View full text |Cite
|
Sign up to set email alerts
|

Tanshinone IIA Selectively Enhances Hyperpolarization-Activated Cyclic Nucleotide–Modulated (HCN) Channel Instantaneous Current

Abstract: Abstract. Tanshinone IIA, one of the main active components from the Chinese herb Danshen, is widely used to treat cardiovascular diseases in Asian countries, especially in China. To further elucidate its heart rate-reducing and anti-ischemic mechanisms, here we investigated the effects of tanshinone IIA on hyperpolarization-activated cyclic nucleotide-modulated (HCN) channels expressed in Xenopus oocytes using two-electrode voltage clamp techniques. When applied to the extracellular solution, 100 μM tanshinon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…89 In addition, KCNE2 increases sensitivity of HCN2 instantaneous current to enhancement by tanshinone IIA, one of the main active components from the Chinese herb Danshen, which has heart rate-reducing and anti-ischemic properties. 90 Human KCNE2 gene variants are also associated with atrial fibrillation; in this case the variants caused a gain of function of KCNQ1-KCNE2 channels when studied in vitro, consistent with a potential role in atrial fibrillation, which can be triggered by shortening of the atrial refractory period. 91 It is not yet known whether KCNQ1-KCNE2 channels form in mammalian heart, but one possible role is for a background K + conductance that could provide an essentially constant repolarizing force, possibly regulated by factors such as pH or cyclic AMP.…”
mentioning
confidence: 52%
“…89 In addition, KCNE2 increases sensitivity of HCN2 instantaneous current to enhancement by tanshinone IIA, one of the main active components from the Chinese herb Danshen, which has heart rate-reducing and anti-ischemic properties. 90 Human KCNE2 gene variants are also associated with atrial fibrillation; in this case the variants caused a gain of function of KCNQ1-KCNE2 channels when studied in vitro, consistent with a potential role in atrial fibrillation, which can be triggered by shortening of the atrial refractory period. 91 It is not yet known whether KCNQ1-KCNE2 channels form in mammalian heart, but one possible role is for a background K + conductance that could provide an essentially constant repolarizing force, possibly regulated by factors such as pH or cyclic AMP.…”
mentioning
confidence: 52%
“…The terpenoid tanshinone IIA from Salvia miltiorrhiza, which was reported to exhibit anticonvulsant effects [139], was also shown to enhance BK Ca channels [140,141], KCNQ1/KCNE1 K + channels [142], and hyperpolarization-activated cyclic nucleotide-gated (HCN) channels [143], and to inhibit glutamate release from rat cortical synaptosomes via the inhibition of presynaptic Ca 2+ entry and inhibition of the mitogen-activated protein kinase (MEK) [144]. Ginsenosides have been shown to interact with a variety of ion channels, including the GABA A receptor (Rg3) [145], KCNQ1 K + channels (Rg3) [146], Na + channels (Rg3) [147], and L-type, N-type, P/Q-type, and T-type Ca 2+ channels [148].…”
Section: Other Ion Channelsmentioning
confidence: 99%
“…The result proved that SephadexG-50 adsorption was also suitable for encapsulation efficiency determination of lipid microsphere. In recent years, many studies have shown that Tan-IIA has certain protection on experimental cerebral ischemia injury [16][17][18] . We had studied the pharmacokinetics in vivo of rats and tissue distribution in vivo of mice of Tan-IIA-LM and STS in our preliminary study [19][20] , the result showed that Tan-IIA-LM in rats in vivo bioavailability degree (AUC), peak concentration (C max ) were 2.38, 2.22 times than the STS, respectively, indicating that Tan-IIA-LM has higher bioavailability compared with STS.…”
mentioning
confidence: 99%